2015
DOI: 10.5380/dma.v34i0.37073
|View full text |Cite
|
Sign up to set email alerts
|

Indígenas e Natureza: a reciprocidade entre os Kaingang e a natureza nas Terras Indígenas Por Fi Gâ, Jamã Tÿ Tãnh e Foxá

Abstract: Artigo recebido em 8 de julho de 2014, versão final aceita em 11 de junho de 2015. RESUMODo ponto de vista demográfico, os Kaingang representam, atualmente, a maior população indígena do Brasil meridional, somando aproximadamente 30 mil indivíduos. O estudo visa analisar aspectos dos indígenas Kaingang e suas relações com a natureza nas Terras Indígenas Por Fi Gâ, em São Leopoldo, Jamã Tÿ Tãnh, em Estrela, e Foxá, em Lajeado, localizadas em áreas urbanas no estado do Rio Grande do Sul. Como fundamentação, util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
1
5
0
3
Order By: Relevance
“…Furthermore, the discussions brought by other studies developed with the Kaingang (VEIGA, 2006;LAPPE;LAROQUE, 2015;BRANDO, 2022) are in line with the perspective of nature's contributions to people, as described in the second chapter of the document on biodiversity and ecosystem services (BRAUMAN et al, 2020), which shows that the interaction of human beings with nature allows the co-production of ecological knowledge and a positive impact on people's quality of life.…”
Section: Human-nature Relationship: Indigenous Peoplessupporting
confidence: 53%
See 3 more Smart Citations
“…Furthermore, the discussions brought by other studies developed with the Kaingang (VEIGA, 2006;LAPPE;LAROQUE, 2015;BRANDO, 2022) are in line with the perspective of nature's contributions to people, as described in the second chapter of the document on biodiversity and ecosystem services (BRAUMAN et al, 2020), which shows that the interaction of human beings with nature allows the co-production of ecological knowledge and a positive impact on people's quality of life.…”
Section: Human-nature Relationship: Indigenous Peoplessupporting
confidence: 53%
“…Considering that interaction with nature is part of the way of life and the construction of the culture of these peoples and understanding the existing plurality between the different indigenous groups, emphasizing the specific understanding of the Kaingang people on the subject is essential. Lappe and Laroque (2015) conducted a study with a Kaingang group from Rio Grande do Sul and observed the need to look at the customs and traditions that have been perpetuated for thousands of generations when trying to understand the interconnections between these people and nature that surrounds them, as the environment and the territory modulate the entire social organization of the community. Ayres (2022) recorded a similar aspect with the Kaingang people of Paraná, highlighting the importance of the indigenous territory for reproducing culture and nature.…”
Section: Human-nature Relationship: Indigenous Peoplesmentioning
confidence: 99%
See 2 more Smart Citations
“…No âmbito local, nacional e internacional, pode-se destacar diversas situações em que esses grupos humanos, embora, delimitados culturalmente, optaram por se autoconstruir dentro de um sistema social abrangente. Nesse sentido, Lappe (2015) destaca as espacialidades sociais e territoriais a partir de um olhar das coletividades Kaingang, Terras Indígenas no Rio Grande do Sul, no sentido da continuidade dos seus costumes, crenças e rituais no processo de contato com a sociedade não indígena. Já Mussi (2006) (IBGE, 2012).…”
Section: Introductionunclassified